Proceedings of International Conference on Robotics and Automation
DOI: 10.1109/robot.1997.606762
|View full text |Cite
|
Sign up to set email alerts
|

On smooth and safe trajectory planning in 2D environments

Abstract: A novel approach to generating optimal smooth piecewise trajectories based o n a new energy memure i s proposed. Given the configurations (position and direction) of two points in the plane, we search for the minimal energy trajectory that minimizes the integral of the squared acceleration opposed to curvature, which has been the predominant energy measure studied in the literature. The smoothness of the optimal trajectory depends on how the tangential and normal components of acceleration vary over a n interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Path smoothness is also an important aspect of planning energy-efficient trajectory. In [52], the authors proposed an optimal smooth and minimal energy trajectory by minimizing the normal and tangential acceleration variation over an interval of time. The work presented in [53] compares trajectories in terms of energy consumption.…”
Section: Investigating Energy Influence On the Navigation Performancesmentioning
confidence: 99%
“…Path smoothness is also an important aspect of planning energy-efficient trajectory. In [52], the authors proposed an optimal smooth and minimal energy trajectory by minimizing the normal and tangential acceleration variation over an interval of time. The work presented in [53] compares trajectories in terms of energy consumption.…”
Section: Investigating Energy Influence On the Navigation Performancesmentioning
confidence: 99%
“…This analysis is then used to generate both an energy optimal path and a velocity trajectory, which further conserves energy. While a complete and detailed energy model can be beneficial, it is well known that preventing large torque variations in motors by smoothing velocity profiles is most fundamental to energy conservation [42,43]. This chapter concentrates on minimizing energy expenditure for a formation of mobile robots in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Timeoptimal trajectory planning of a mobile agent was studied in Lau et al [2009], where the generated trajectory has continuous curvature. The change of trajectory curvature was also used as the smoothness criterion in the trajectory planning Hussein and Elnagar [1997]. It was reported that the energy consumption could be minimized through optimizing the control inputs along the trajectory Guo andTang [2008]-Howard andKelly [2007], subject to boundary conditions of arrival time and velocity/acceleration at the start and end positions.…”
Section: Introductionmentioning
confidence: 99%